miR‐1322 regulates Ch REBP expression via binding a 3′‐ UTR variant (rs1051943) - Zhang, Ying; Hu, Sen‐Lin; Hu, Dong; Jiang, Jian‐Gang; Cui, Guang‐Lin; Liu, Xing‐De; Wang, Dao Wen (Journal of cellular and molecular medicine, 2018)
The carbohydrate response element‐binding protein (Ch REBP ), also referred to as MLXIPL , plays a crucial role in the regulation of glucose and lipid metabolism. Existing studies have shown an association between genetic variations of the Ch REBP gene and lipid levels, such as triglycerides and high‐density lipoprotein cholesterol. However, mechanistic studies of this association are limited. In this study, bioinformatic analysis revealed that the polymorphism rs1051943A occurs in the complementary binding sequence of miR‐1322 in the Ch REBP 3′‐untranslated region ( UTR ). Studies of potential mechanisms showed that the A allele could facilitate miR‐1322 binding, and luciferase activity significantly decreased when co‐transfected with a Ch REBP 3′‐ UTR luciferase reporter vector and miR‐1322 mimics in HepG2 cells. Furthermore, miR‐1322 significantly regulated the expression of Ch REBP downstream genes and reduced the synthesis of lipids. The expression of miR‐1322 was up‐regulated by glucose and palmitic acid stimulation. Population studies showed that rs1051943‐A allele was only found in the Han Chinese and Uighur ethnic groups, different from European populations (G allele frequency = 0.07). In summary, we provide evidence that the rs1051943 A allele creates a functional miR‐1322 binding site in Ch REBP 3′‐ UTR and post‐transcriptionally down‐regulates its expression, possibly associated with levels of plasma lipids and glucose.